Sociological theory - Ritzer, George; Stepnisky, Jeffrey (New Delhi Sage India, 2022)
Sociological Theory gives readers a comprehensive overview of the major theorists and schools of sociological thought, from sociology's 19th century origins through to the early 21st century. Written by an author team that includes one of the leading contemporary thinkers, the text integrates key theories with biographical sketches of theorists, placing them in historical and intellectual context.